The effects of rose bengal- and erythrosine-mediated photodynamic therapy on Candida albicans - Borges Pereira Costa, Anna Carolina [UNESP]; Campos Rasteiro, Vanessa Maria [UNESP]; Pereira, Cristiane Aparecida [UNESP]; Rossoni, Rodnei Dennis [UNESP]; Junqueira, Juliana Campos [UNESP]; Cardoso Jorge, Antonio Olavo [UNESP] (Wiley-Blackwell, 2012)
The aim of this study was to evaluate the effects of photodynamic therapy (PDT) using rose bengal or erythrosine with light emitting diode (LED) on Candida albicans planktonic cultures and biofilms. Seven C. albicans clinical strains and one standard strain (ATCC 18804) were used. Planktonic cultures and biofilms of each C. albicans strain were submitted to the following experimental conditions: (a) treatment with rose bengal and LED (RB+L+); (b) treatment with erythrosine and LED (E+L+); and (c) control group, without LED irradiation or photosensitiser treatment (P-L-). After irradiation of the planktonic cultures and biofilms, the cultures were seeded onto Sabouraud dextrose agar (37 degrees C at 48 h) for counting of colony-forming units (CFU ml-1) followed by posterior anova and Tukeys test analyses (P < 0.05). The biofilms were analysed using scanning electron microscopy (SEM). The results revealed a significant reduction of planktonic cultures (3.45 log10 and 1.97 log10) and of biofilms (<1 log10) for cultures that were subjected to PDT mediated using either erythrosine or rose bengal, respectively. The SEM data revealed that the PDT was effective in reducing and destroying of C. albicans blastoconidia and hyphae. The results show that erythrosine- and rose bengal-mediated PDT with LED irradiation is effective in treating C. albicans.
Keywords: Candida albicans; erythrosine; rose bengal; light emitting diode; photodynamic therapy; biofilm